Os professores como autores de suas práticas: A pesquisa-Ação na construção coletiva de um livro na educação física - Rufino, Luiz Gustavo Bonatto [UNESP] (My University, 2017)
In this study, we aimed to analyze the process of collective production of a textbook in Physical Education, made by five teachers in different stages of their career. They participated in an in-service training process based on the development of reflections about pedagogical practice. For this, we chose a qualitative approach based on an action-research with the collaborators. In addition to the registration of the meetings, there were classroom observations, amplifying data analyzes. Two categories emerged from the triangulation through content analysis: difficulties, with the subcategories: content systematization in Physical Education; the importance to implement activities proposed; difficulties in writing and materializing the ideas; and possibilities, with the subcategories: forms of using and intermediation of pedagogical actions; supporting elements of teaching training; the collective production of textbooks. We concluded that propositions, such as the one presented, tend to be significant once it starts from the ground of practice and has the teachers as their authors, developing a culture of collaboration. At the same time, it works with professional knowledge, conceiving the school as a place of knowledge production. Finally, it contributes to the construction of a teaching practice epistemology.
Keywords: Collaborative research; Continuing education; Pedagogical practice; Professional practice; School physical education; Textbook